Bexarotene: A Novel Drug Delivery System for Cutaneous T-cell Lymphoma (CTCL) - Kamboj, Anjoo; Arockia Babu, M Arockia Babu (International Journal of Psychosocial Rehabilitation, 2019)
Bexarotene is an analogue which is used as skin manifestations therapy of the “cutaneous T-cell lymphoma (CTCL)”. Its therapy is highly associated with the enhancement in the concentration of serum enzyme and reduces the chances of acute liver iunjury. “Cutaneous T-cell lymphoma (CTCL)” is a member of the family “non-Hodgkin lymphomas” (which are related to the B-cells), and is caused by the mutation of T-cells. They are predominantly found in the skin and are a heterogeneous and relatively rare family of extranodal non-Hodgkin's lymphomas (NHLs). Some patients have dermal spots, plaques, tumors and erythroderma more rarely. The most important prognostic factors in CTCL patients are the type of skin lesions and the surface extent of skin infection and extracutaneous disease. Early-stage patients can only be treated effectively by skin-directed therapies. In this paper, we have talked about the development and characterization of Polymeric-zeinnanomicelles base formulation of Bexarotene for the treatment of “cutaneous T-cell lymphoma (CTCL)”. The Pegylated-zeinnanomicelles were evaluated as nanocarriers to improve the efficacy, reduced toxicity in vivo, protection of encapsulated agent against degradation and enhanced water solubility of hydrophobic bexarotene as a novel delivery system for “cutaneous Tcell lymphoma (CTCL)”. For this, the formulation of nanomicelle drug delivery comprising the Pegylatedzeinnanomicelles encapsulates the bexarotene in two different ratios and then the results were evaluated accordingly.